Klinik Baca Metode Multisensori di Lembaga Kesejahtraan Sosial Anak Budi Mulia Bangunrejo Plosoklaten Kediri - Kubbatul Choiriyah; Khoirotul Izzah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2023)
The Reading Clinic is a forum for students who are still lacking in mastering basic skills, precisely skills in terms of reading and writing which are focused on low grades at LKSA Budi Mulia Plosoklaten The purpose of writing this article is to increase interest in reading in students with multisensory methods for difficulty learning to read and write. The learning method that learners need to help overcome reading difficulties is a method that can function the entire senses to recognize or learn something, namely the mutisensory method. In the study itself, the author chose to use the PAR (Participatory Action Research) method. As a result of this study, some children were able to adapt the material, create works and have a high interest in reading.